Pemanfaatan Museum Sebagai Wisata Edukasi dan Media Pembelajaran Sejarah - Fifit Fitriansyah; Kasmin Kasmin (Cakrawala - Jurnal Humaniora, 2022)
The museum is actually a historical place that is most visited by tourists. But now it's different, the Covid 19 pandemic has made the museum's existence seem to be suspended. A museum among teenagers, in this case the students themselves, seems to be a rare item that is rarely visited. Whereas the existence of the museum can be used as an educational tour for the community and a medium for learning history for students. This study aims to use the museum as an educational tour and learning media, especially in learning history. The method used in this research is descriptive qualitative which describes the findings in the field. In this study also used the survey method to see student responses. The results of this study found that 88.90% of students agree that museums are educational tours and 93% of students agree that museums can be used as a medium for learning history. By utilizing museums as educational tours and historical learning media, it can increase students' interest in visiting museums and achieve optimal learning goals.